1989
DOI: 10.1002/mar.4220060406
|View full text |Cite
|
Sign up to set email alerts
|

Black and white response to culturally targeted television commercials: A values‐based approach

Abstract: This study examines the effect of four national television advertisements for product category leader brands. These ads were developed expressly for black consumers. Through the use of cultural values, responses to ethnic or subculturally oriented marketing communication was measured. Two hundred and seventy one black and white respondents were drawn from a large urban, mid‐western city and a midsize deep‐south city. Multivariate analysis of variance was used to determine the differences between responses to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…This stream of research has found that ethnic group identification operates as a type of reference group and does exert both normative and informational influence on an individual's behavior and attitudes (Donthu & Cherian, 1994;Kara & Kara, 1996;Pitts, Whalen, O'Keefe, & Murray, 1989;Williams & Qualls, 1989). The identification of racial cues in advertisements also seems to be influenced by the level of ethnic identification.…”
Section: Heuristic Processing and Ethnic Identificationmentioning
confidence: 99%
“…This stream of research has found that ethnic group identification operates as a type of reference group and does exert both normative and informational influence on an individual's behavior and attitudes (Donthu & Cherian, 1994;Kara & Kara, 1996;Pitts, Whalen, O'Keefe, & Murray, 1989;Williams & Qualls, 1989). The identification of racial cues in advertisements also seems to be influenced by the level of ethnic identification.…”
Section: Heuristic Processing and Ethnic Identificationmentioning
confidence: 99%
“…Even if minority consumers do not have special needs for certain products, they are more responsive to messages that emphasize their unique values and cultural heritage. Several studies find that ethnic consumers are more receptive to advertising focusing on aspirations and values that are salient to them, such as self-fulfillment, self-respect, and accomplishment (Pitts, Whalen, O'Keefe and Murray 1989). Minority consumers also perceive that advertisements using ethnic models project a higher quality image (Kerin 1979).…”
Section: Ethnocentric Biasmentioning
confidence: 98%
“…Fairchild, Stockard and Bowman (1986) demonstrate that African Americans seek out programming that includes representatives of their own ethnic group or portrays ethnically relevant life experiences (Howard, Rothbart, & Sloan, 1978;Hur, 1978). Advertising targeting African American cultural values and using models perceived as similar to observers has been shown to be more effective with this group (Pitts, Whalen, O'Keefe, & Murray, 1989;Rokeach, 1960). It is clear that many African Americans are more likely to attend carefully to HIV prevention messages delivered by people of color than by White, male, middle-class experts (De La Cancela, 1989;DiClemente & Houston-Hamilton, 1989).…”
Section: Sociocultural Factors and Perceptions Of Sourcesmentioning
confidence: 99%
“…Advertising targeting African American cultural values and using models perceived as similar to observers has been shown to be more effective with this group (Pitts, Whalen, O'Keefe, & Murray, 1989;Rokeach, 1960). It is clear that many African Americans are more likely to attend carefully to HIV prevention messages delivered by people of color than by White, male, middle-class experts (De La Cancela, 1989;DiClemente & Houston-Hamilton, 1989).…”
Section: Sociocultural Factors and Perceptions Of Sourcesmentioning
confidence: 99%